Sesmarias, índios e conflitos de terra na expansão portuguesa no Vale do Parnaíba (Maranhão e Piauí, séculos XVII e XVIII) - ROLAND, Samir Lola (Universidade Federal do Pará, 2019)
In the captaincies of Maranhão and of Piauí, in Portuguese America, there were the target of the expansion of the frontier of conquest and occupation of lusomaranhense and lusobaiana from the end of the 17th century until the first half of the 18th century. This dissertation deals with this new territorial organization that occurred during the Portuguese expansion in the region. The research tries to analyze how the space of the captaincies of Maranhão and Piauí is represented in the course of the process of conquest and occupation of the region. The dissertation discusses how the authorities and residents perceived the space that was being disputed with the various indigenous groups. Another discussion carried out by the dissertation deals with the land conflicts between sesmeiros and squatters during the distribution of letters of sesmarias by the governors of the State of Maranhão, as well as the actions and decisions of the Portuguese Crown with respect to the planning of the occupation and the settlement in the period listed.